Validity and reliability of pencak silat achievement motivation instrument - Gandinni, Nanda Aprilia; Guntoro, Tri Setyo; Watiningsih, Rita; Nurhidayah, Dewi (Jurnal Ilmu Keolahragaan, 2025)
Background. Achievement motivation plays a crucial role in the performance of martial arts athletes and should be closely monitored and assessed by coaches. However, the absence of a specific instrument to measure achievement motivation in Setia Hati Terate athletes has made it difficult for coaches to evaluate their athletes"™ motivational levels effectively. Objectives. This study is part of a broader evaluation aimed at testing the validity and reliability of an achievement motivation questionnaire specifically designed for adult Pencak Silat practitioners. Methods. The study involved 162 participants, comprising 79 male and 83 female martial artists. A research instrument is a tool used to gather data in order to address research problems or meet study objectives. If the collected data are not accurate (i.e., valid), any conclusions or decisions based on them will also be flawed. In this study, a closed-ended questionnaire consisting of 14 items was used. Data analysis was conducted using Confirmatory Factor Analysis (CFA). CFA conclusions are drawn based on various fit indices, including chi-square (Ï‡ ²), degrees of freedom (df), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), Goodness-of-Fit Index (GFI), Standardized Root Mean Residual (SRMR), Root Mean Square Error of Approximation (RMSEA), factor loading (Î»), Average Variance Extracted (AVE), and Cronbach's alpha. Results. According to the fit indices shown, the chi-square test yielded a p-value < 0.001, indicating a significant relationship between the factors. These indicators confirm the model"™s good fit. Further analysis of factor loadings and reliability metrics indicates that the instrument is both valid and reliable, supporting its use in assessing achievement motivation among adult martial arts practitioners. Conclusion. Achievement motivation is essential for martial artists striving to reach their full potential. Therefore, evaluating motivation levels should be an integral part of every stage in the training program, using instruments that are both valid and reliable. This study serves as a foundation for the ongoing development of assessment tools in the martial arts field.